(untitled) (Journal of Engineering, 2013)
In this study three reactive dyes (blue B, red R and yellow Y) in single , binary and ternary solution were adsorbed by activated carbon AC in equilibrium and kinetic experiments. Surface area, Bulk and real density, and porosity were carried out for the activated carbon. Batch Experiments of pH (2.5-8.5) and initial concentration (5-100) mg/l were carried out for single solution for each dye. Experiments of adsorbent dosage effect (0.1-1)g per 100 ml were studied as a variable to evaluate uptake% and adsorption capacity for single dyes(5, 10) ppm, binary and ternary (10) ppm of mixture solutions solution of dyes. Langmuir, and Freundlich, models were used as Equilibrium isotherm models for single solution. Extended Langmuir and Freundlich were used of multi-dyes solutions. Kinetic (contact time) experiments carried out for single dyes (5, 10)ppm, binary and ternary(10) ppm of mixture solutions at dosage of adsorbent 5 g/l and pH(6.2-6.7) in order to investigate the fitting with the kinetic models (pseudo first and second order) and intrapartical to determine the mechanism of transfer the molecules of dye from bulk phase to solid phase. Beer law principle and modified method Multi linear Regression (MLR) was used for single, binary and ternary dyes solutions